Yahoo奇摩 網頁搜尋

  1. In statistics, the kth order statistic of a statistical sample is equal to its kth-smallest value...other sample quantiles. When using probability theory to analyze order statistics of random samples from a continuous distribution, the cumulative distribution...

    分類:科學及數學 > 數學 2008年04月11日

  2. You can think them as the composition of two fn.(except the order of operation). (12): 1 -> 2, 2 -> 1 (123): 1 -> 2, 2->3 , 3->1 (123...

    分類:科學及數學 > 數學 2010年10月21日

  3. yes, there are some methods for solving those type of 2nd order differential equations. for example , for the product rule 2nd order differential equation...

    分類:科學及數學 > 數學 2008年04月29日

  4. 我做到個答案但要12:00先post到﹐另外那條未有頭緒﹐又無答案 2008-03-29 00:05:25 補充: use the formula we get g(y1)=n(1-y1)^(n-1) g(yn)=n(yn)^(n-1) g(y1yn)=n(n-1)(yn-y1)^(n-2) Consider Beta distribution E(y1)=n/(n+1) E(yn)=1/(n+1) E(y1yn) =∫∫y1yn n(n-1)(yn-y1)^(n-2) dyndy1...

    分類:科學及數學 > 數學 2008年04月01日

  5. y'' + y = tan x   yh = c1cos x + c2sin x ~ homogenous solution  Let Q = tan x    yp = u1y1 + u2y2 = u1 cos x + u2 sin x  W =│ cos x sin x │= 1    │- sin x cos x│  u1 =∫( - y2Q/W )dx    =∫- sin x tan x dx =∫( cos x - sec x )dx    = sin x - ln│sec x + tan...

    分類:科學及數學 > 數學 2010年12月03日

  6. a) 1 < -13/-9 b) -3/2 > -2^2 c) -13/-9 > 1 > 0 > -3/2 > -2^2 2)多項式polynomial個degree(即次方既數字)一定要係positive integer a) x+2 在分母姐係 -1次方 b) 不是整數的次方

    分類:科學及數學 > 數學 2013年07月30日

  7. For each y, F(y) = y, f(y) = 1 , as they are U[0,1] For Y(m) , P( Y(m) <= y ) = P( Y1 <= y, Y2 <= y , ... , Ym <= y ) [ Since Y(m...

    分類:科學及數學 > 數學 2010年10月14日

  8. If y never appear in a differential equation, it's order can be reduced by 1 by using the following trick 圖片參考:http://i187.photobucket.com/albums/x22/cshung/7008031200447.jpg

    分類:科學及數學 > 數學 2008年03月13日

  9. http://img502.imageshack.us/img502/285/78279861.png 圖片參考:http://img502.imageshack.us/img502/285/78279861.png

    分類:科學及數學 > 數學 2010年12月12日

  10. λ² - 2λ + 1 = 0 λ = 1 , 1 yh = c1*e^t + c2*te^t Let y1 = e^t , y2 = te^t , f = (e^t)/t W( y1 , y2 ) = y1*y2' - y2*y1' = e^t*( e^t + te^t ) - te^t*e^t = e^(2t) u1' = - y2 * f / W = - te^t * [ (e^t)/t ] / e^(2t) = - 1 u1 = - t u2' = y1 * f / W = e^t * [ (e^t)/t ] / e^(2t) = 1/t u2...

    分類:科學及數學 > 數學 2016年12月11日